Utilization of Instagram Social Media at GMF AeroAsia TBK - Tarigan, Rini Suryani; Khohar, Abdul; Hariyati, Farida (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the use of Instagram social media at the GMF AeroAsia company to find out that the use of Instagram social media is an important strategy for companies in building brand image, increasing customer engagement, expanding market reach, and attracting the attention of Generation Z. by exploring Instagram social media by the GMF AeroAsia company , one of the industry leaders in aircraft maintenance utilization in Asia. Key findings include diverse content strategies, including the use of high-quality photos and videos to showcase the company's services, products and operational activities. Not only that, the use of social media on Instagram has made this company increasingly known to many people. Previously, the GMF AeroAsia company had not used Instagram social media as an adaptation to today, making the GMF AeroAsia company name fade, but slowly the GMF AeroAsia company name is fading. The GMF AeroAsia company is starting to rise by adapting to social media and utilizing Instagram social media. Then GMF AeroAsia's Instagram social media actively interacts with its followers through various interactions, such as answering customer questions, providing the latest information about aircraft maintenance services, and holding contests or special events to increase user engagement. The research method used is a qualitative method with a case study approach. The data collection techniques that the author uses in this research are interviews with company social media managers, observation and documentation. However, there are challenges in maintaining consistent content and increasing user engagement on an ongoing basis